Astrocytic Orosomucoid-2 Modulates Microglial Activation and Neuroinflammation - Jo, Myungjin; Kim, Jong-Heon; Song, Gyun Jee; Seo, Minchul; Hwang, Eun Mi; Suk, Kyoungho (SOC NEUROSCIENCE, 2017)
Orosomucoid (ORM) is an acute-phase protein that belongs to the immunocalin subfamily, a group of small-molecule-binding proteins with immunomodulatory functions. Little is known about the role of ORM proteins in the CNS. The aim of the present study was to investigate the brain expression of ORM and its role in neuroinflammation. Expression of Orm2, but not Orm1 or Orm3, was highly induced in the mouse brain after systemic injection of lipopolysaccharide (LPS). Plasma levels of ORM2 were also significantly higher in patients with cognitive impairment than in normal subjects. RT-PCR, Western blot, and immunofluorescence analyses revealed that astrocytes are the major cellular sources of ORM2 in the inflamed mouse brain. Recombinant ORM2 protein treatment decreased microglial production of proinflammatory mediators and reduced microglia-mediated neurotoxicity in vitro. LPS-induced microglial activation, proinflammatory cytokines in hippocampus, and neuroinflammation-associated cognitive deficits also decreased as a result of intracerebroventricular injection of recombinant ORM2 protein in vivo. Moreover, lentiviral shRNA-mediated Orm2 knockdown enhanced LPS-induced proinflammatory cytokine gene expression and microglial activation in the hippocampus. Mechanistically, ORM2 inhibited C-C chemokine ligand 4 (CCL4)-induced microglial migration and activation by blocking the interaction of CCL4 with C-C chemokine receptor type 5. Together, the results from our cultured glial cells, mouse neuroinflammation model, and patient studies suggest that ORM2 is a novel mediator of astrocyte-microglial interaction. Wealso report that ORM2 exerts anti-inflammatory effects by modulating microglial activation and migration during brain inflammation. ORM2 can be exploited therapeutically for the treatment of neuroinflammatory diseases.
Keywords: HUMAN ALPHA-1-ACID GLYCOPROTEIN; MULTIPLE-SCLEROSIS; ALPHA(1)-ACID GLYCOPROTEIN; ALZHEIMERS-DISEASE; BRAIN-INJURY; ALPHA1-ACID GLYCOPROTEIN; INFLAMMATORY RESPONSE; MOUSE MODELS; CELLS; EXPRESSION